Effects of mechanical power fluctuation on power system stability - Kim W.S.; Hashim H.; Omar Y.R.; Izham I.Z. (2023)
Fluctuation of mechanical power is known to be one of many major factors affecting stability of a power plant and the power system network connected to it. The occurrence of this fluctuation is due to the inconsistent input supply to the prime mover, mechanical failure and control system itself such as the process of quick operation of steam turbine governing, which would cause the pressure oscillation in turbine steam inlet pipeline. Consequences of this fluctuation may trigger situations such as power system low frequency oscillation and loss of synchronism, which can occur if the speed oscillation experienced by the machine exceeds its allowable limits. As a result, protection system will react, which causes the generator to be taken off line from the system. This paper presents the evaluation on the effects of mechanical power fluctuation on the power system stability based on turbine gain in static and dynamic load environment. 2010 IEEE.